If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -1(x + 6) = 9x + -5 Reorder the terms: 11 + -1(6 + x) = 9x + -5 11 + (6 * -1 + x * -1) = 9x + -5 11 + (-6 + -1x) = 9x + -5 Combine like terms: 11 + -6 = 5 5 + -1x = 9x + -5 Reorder the terms: 5 + -1x = -5 + 9x Solving 5 + -1x = -5 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 5 + -1x + -9x = -5 + 9x + -9x Combine like terms: -1x + -9x = -10x 5 + -10x = -5 + 9x + -9x Combine like terms: 9x + -9x = 0 5 + -10x = -5 + 0 5 + -10x = -5 Add '-5' to each side of the equation. 5 + -5 + -10x = -5 + -5 Combine like terms: 5 + -5 = 0 0 + -10x = -5 + -5 -10x = -5 + -5 Combine like terms: -5 + -5 = -10 -10x = -10 Divide each side by '-10'. x = 1 Simplifying x = 1
| 6x-14=6x+56 | | X^2=3400 | | -15n-40=23-8n | | 8y-4-3y+2=0 | | (Z/4)=6 | | 2x+1=3x+46 | | F(h)=35h+215 | | 4x+1+4x+4=89 | | 13-x-x=27 | | 8x-4-4x=2x+4 | | 3/4x+4=5/6x | | x^6-4x^3+3=0 | | 7+5x+2x-14=-21 | | 2x-8=-8+2x | | 2x+10=8x-1 | | 2x+1=3x-31 | | 3x/8+1=x/3-1/2 | | 25x-9=50x+11 | | 6x-(x-10)=-15 | | -12/(6/5x) | | 14x+1+4-2+2=89 | | -12/6/5x | | 9w+3=7w | | -3-8(6-8x)=-109 | | 7x-3(x+4)=-16 | | -x/2=26 | | -8x+9=-31 | | 6x+4=4x-26 | | .25x-.375x=2 | | 7y+12=5y-2 | | 6x+4+4x=-26 | | 4n+(7+n)=52 |